The designer's dictionary of color 2026-02-16T18:10:12+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Adams, Sean (Abrams, 2017)

(untitled)
The Designer's Dictionary of Colour provides an in-depth look at 30 colours key to art and graphic design. Organized by spectrum, in colour-by-colour sections for easy navigation, this book documents each hue with charts showing colour range and palette variations